Legal Protection Registered Industrial Design Under The Act Number 31 Of 2000 On Industrial Design - Desi Ana Yustianita; Munsharif Abdul Chalim (Jurnal Daulat Hukum, 2019)
In recent years, in some cases frequent abuse, which mimics the design industries of some of the industrial design is registered and Industrial Design Rights, causing economic losses to the owner of Right to Industrial Design. This study aims to find out about the legal protection of industrial designs by Act Number 31 of 2000 on Industrial Designs. This study uses normative juridical approach, namely legal research conducted by coating researching library materials or secondary data by means of a search against regulations and literatures relating to studied problem.Result and discussion and analysis that the Legal Protection of Industrial Design by Act Number 31 of 2000 on design has a term of 10 years in accordance with Article 5 (1) Number 31 of 2000 on Industrial Designs.Keywords: Legal Protection; Industrial Designs and Legal Protection.